Does innovativeness reduce startup survival rates? - Hyytinen, Ari; Pajarinen, Mika; Rouvinen, Petri (Journal of Business Venturing, 2015)
There are two competing hypotheses explaining how innovativeness influences the survival of startups: On the one hand, innovativeness is argued to foster survival-enhancing attributes (e.g., market power and cost efficiency) and capabilities (e.g., absorptive capacity). On the other hand, an innovative startup faces (and bears the associated risks of) liabilities of newness and smallness that exceed those of its non-innovative counterparts. The available empirical literature addressing this theoretical tension mostly supports the former hypothesis; we suggest that this finding is, in part, driven by the common practice of employing an ex post measure that already embodies a degree of success in innovativeness. We use an ex ante measure and find that a startup's innovativeness is negatively associated with its subsequent survival. We also find that entrepreneurs' greater appetite for risk magnifies this negative association. These findings imply that pursuing innovations is not necessarily associated with survival during the early stages of firm development and entails a more complicated start-up process.